The Effects of Adipose Derived Stromal Vascular Fraction and Platelet-Rich Plasma on Bone Healing of a Rat Model With Chronic Kidney Disease. Issue 3 (September 2020) - Eyuboglu, Atilla Adnan; Arpaci, Enver; Albayati, Abbas; Uysal, Ahmet Cagri; Terzi, Aysen; Bozalioglu, Sema; Turnaoglu, Hale; Balcik, Cenk; Ozkan, Burak; Ertas, Nilgun Markal
Abstract : Background: Chronic kidney disease (CKD) impairs osteoblast/osteoclast balance and damages bone structure with diminished mineralization and results in bone restoration disorders. In this study, we investigate the effects of adipose-derived stromal vascular fraction and platelet-rich plasma (PRP) on bone healing model in rats with CKD. Methods: Sprague-Dawley rats were separated into 4 groups. All groups except group I (healthy control) had CKD surgery using 5/6 nephrectomy model. All groups had intramedullary pin fixation after receiving bone fracture using drilling tools. Group II rats were used as control group for CKD. Group III rats received PRP treatment on fracture site. Group IV rats received PRP and stromal vascular fraction treatment on fracture site. Weight loss and blood samples were followed at the time of kidney surgery, third, sixth, and 12th weeks. Bone healing and callus formations were compared, biomechanically, radiologically, histopathologically, and immunohistochemically. Osteoblastic transformation of stem cells was assessed with DiI staining. Results: Negative effects of CKD on bone healing were reduced by increasing mechanical, histological, radiological, and biochemical properties of the bone with stromal vascular fraction and PRP treatments. Although thickness of callus tissue delayed bone healing process, it also enhanced biomechanical features and bone tissue organization. Conclusions: Platelet-rich plasma and adipose-derived stromal vascular fraction treatments were effective for bone healing in animal model, which can be promising for clinical trials. Abstract : Supplemental digital content is available in the text.